Assays to Assess Autophagy Induction and Fusion of Autophagic Vacuoles with a Degradative Compartment, Using Monodansylcadaverine (MDC) and DQ-BSA - Vázquez, Cristina Lourdes (2009)
In this chapter we describe the use of monodasylcadaverine (MDC) and DQ-BSA, two practical and convenient tools to study the autophagic pathway. MDC is a lysosomotropic compound useful for the identification of autophagic vesicles by fluorescence microscopy and, in addition, to assess autophagy induction via the accumulation of MDC-labeled vacuoles. However, the increase of autophagosomes does not necessarily reflect autophagosome maturation and degradation of the sequestered materials, thus the use of DQ-BSA in conjunction with and autophagic marker is an appropriate technique to monitor the formation of the autolysosome, the degradative compartment. Therefore, here we discuss the advantages of the utilization of these two methods to characterize the autophagy pathway.